(untitled) (Islamic Sciences Journal, 2023)
Islamic legislations clarified what is valid for marriage and what is suitable for a marriage contract. God has made it clear in the Qur’an, and the Holy Prophet also clarified that in authentic hadiths. Accordingly, incest is a guilt that necessitates the punishment for adultery. And the prohibition of committing its preludes and causes and approaching it; and the prohibition of things that are close to it as well, such as mixing, singing, dancing, drugs and intoxicants and the like. By considering it one of the greatest immoralities and one of the greatest sins, and comparing it with polytheism with God Almighty and killing souls. Islamic legislation intends from that to protect one’s honor and protect it from corruption and disruption and interference, because pure symptoms require happy peacefulness in the family. Incest is forbidden and is not accepted by the human soul and in all heavenly religions.